(untitled) (Journal of Management and Social Sciences, 2024)
Abstract Nigeria’s democratic transition has been hampered by a number of issues, such as political instability and election rigging. The paper examines the causes of election rigging in south-west Nigeria, investigating how election rigging and political instability contributed to the collapse of the democratisation process in south-west Nigeria, and examines the extent to which a well-organised electoral system can affect political stability in south-west Nigeria. The study adopts a survey research design. The population of the study comprises students from Osun State University, Osogbo, Osun State, and the University of Ibadan, Ibadan, Oyo State. A sample size of one hundred and twenty political science students was purposively selected from the two universities. Sixty students were randomly selected from each of the two universities. A questionnaire was used to collect data.The collected data was analysed using descriptive statistical tools. Findings of the study revealed that political instability and election rigging can have a detrimental effect on south-west Nigeria’s democratisation efforts. The finding also shows that a well-organised electoral system in south-west Nigeria can bring about political stability by promoting transparency, accountability, and legitimacy. The study therefore concludes that elections in the future must be seen as being more orderly, less violent, and a truer reflection of the choices made by voters than those in the past. Keywords Election, election rigging, political instability, democratisation, South-West